PEMANFAATAN URINE MANUSIA MENJADI PUPUK ORGANIK CAIR UNTUK TANAMAN PAKCOY (Brassica chinensis L.) - Amin, Radjali; Fataha, Malik; Fandeli, Chafid (Departement of Agrotechnology, Agriculture Faculty, Universitas Lampung, 2024)
The need for more healthy food is increasing in line with population growth and human awareness. The use of fertilizers to increase productivity is a must and the choice of using organic fertilizers can be a solution to answer that need. Human urine has the potential to become liquid organic fertilizer (LOF). The objective of the study was to compare the growth of B. chinensis treated with human urine LOF, NPK fertilizer, and well water as the control, and to determine the best concentration of LOF. This research was conducted experimentally using a complete randomized design (CRD) with three repetitions. The treatments applied in this study were the treatment of LOF concentration variations with doses of 5 ml/1, 20 ml/1, 35 ml/1, 50 ml/1 and 65 ml/1, NPK fertilizer 10 grams/1 and well water. The data from this study were tabled, then analyzed descriptively, ANOVA analysis, and DMRT. The fermented LOF increased N by 0.6%, P2O5 by 0.8%, K2O by 0.9%. It was concluded that the best treatment in the growth of B. chinensis, which was observed from the parameters of width of leaf, height, wet weight, dry weight of plants, was in the treatment of NPK fertilizer 10 grams/1 and followed by LOF treatment 65 ml/1. The number of leaves parameter was less representative in expressing the impacts of LOF treatment, NPK fertilizer, and even the Well Water Treatment.